Investigating the Role of Internet of Things in Knowledge Management Systems (Case Study: Offering A Resource Description Model Based on Ontological Study of Smart Store Management (Smart Shopping Cart) - Shahpasand, Siamak; Rahimzadeh, Omid (International Journal of Engineering and Technology, 2018)
Rapid changes in the knowledge management (KM) area are substantially dependent on the considerable progresses made by the mankind in the information technology (IT) during these years. In fact, Internet of Things (IoT), as part of the applied technologies in the IT world, has rendered feasible the fast growth and sharing of knowledge. IoT records the data pertinent to the natural phenomena and classifies and calculates them for the purpose of facilitating a better and easier perception thereby to enable the human beings better perceive the phenomena. The quality of achieving an integrated source in regard of resource description is an important challenge in IoT for a large number of heterogeneous devices.According to the absence of an integrated description model for IoT devices, the present article tries proposing an ontology-based resource description model (ORDM). These resources in IoT include the description of such classes as specifications, statuses, controls, situations, performances, histories and privacies inherent of the things. The ontology-based description model (ORDM) can be completely implemented for the performance optimization of a smart store through its offering of a smart shopping cart. The experiment results indicated that the proposed model is of a considerable applied value and prospect in the optimization of devices’ access and business performance in IoT.